Remote education to deaf students in pandemic times - Shimazaki, Elsa Midori; Menegassi, Renilson José [UNESP]; Fellini, Dinéia Ghizzo Neto (Universidade Estadual de Ponta Grossa (UEPG), 2020)
Since the Covid-19 outbreak in Brazil, changes occurred to face this pandemic and social isolation (lockdown) is one. The State of Paraná implemented remote education showing concerns of the school community regarding the teaching and learning of deaf students. Therefore, latent concerns led to a punctual and exploratory remote study. Five teachers, three students and one pedagogue from a school of foreign language education were questioned using three different questionnaires with six questions each and one oral interview. Results, supported by historical-cultural theories and dialogism in language, show: a) Remote teaching classes preparation is a challenge; b) some economically vulnerable students do not have access to remote activities; c) students without parental assistance to study; d) difficulty to understand and interpret the statements; e) without school social contact, isolation affects the linguistic and social development of deaf students.
La educación remota a los estudiantes sordos em tiempos pandémicos
Ensino remoto para alunos surdos em tempos de pandemia
Keywords: Deaf student; Development; Remote teaching